Job Involvement and its role in promoting organizational citizenship behavior: An analytical study of the opinions of a sample of Northern Technical University employees (NTU journal for Administrative and Human Sciences (JAHS), 2025)
The current research aimed to diagnose the role of job Involvement in promoting organizational citizenship behavior at the Northern Technical University. The research problem centered on showing the availability of dimensions of job Involvement, which has a significant impact on the behavior of organizational citizenship, and the following questions branch out from it: What is the impact of activity on the behavior of organizational citizenship? What is the impact of dedication on organizational citizenship behaviors? What is the effect of engagement on organizational citizenship behaviors? In order to achieve the desired goal of the research, several main and sub-hypotheses were formulated, and the research adopted the descriptive approach in presenting intellectual and theoretical frameworks, as well as the analytical approach within the field side of the research to process, analyze, and interpret data. As for the research sample, it was intentionally chosen from administrative individuals in administrative positions within the different organizational levels in the researched organization, and they numbered (129) individuals. The questionnaire was used as a main tool in data collection, and a number of statistical methods were used to process the field side data, and to test the research hypotheses. Or regional and international, in light of the intensification of competition, the importance of studying the factors that would increase the immersion of workers in their organizations, which contributes to strengthening their organizational citizenship behavior.